2020
DOI: 10.1038/s41467-020-15674-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mismatched and wobble base pairs govern primary microRNA processing by human Microprocessor

Abstract: MicroRNAs (miRNAs) are small RNAs that regulate gene expression. miRNAs are produced from primary miRNAs (pri-miRNAs), which are cleaved by Microprocessor. Microprocessor, therefore, plays a crucial role in determining the efficiency and precision of miRNA production, and thus the function of the final miRNA product. Here, we conducted highthroughput enzymatic assays to investigate the catalytic mechanism of Microprocessor cleaving randomized pri-miRNAs. We identified multiple mismatches and wobble base pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 49 publications
6
62
0
Order By: Relevance
“…The effect of bulges in the midB_1013 is similar to that of mismatches and wobble base pairs found in the previous study [19]. Therefore, we examined the effect of bulges in Bar charts to show the unproductive/productive ratios or cleavage efficiency (i.e.…”
Section: The Midb_89 On the 3p-strand Influences The Cleavage Sites Osupporting
confidence: 57%
See 1 more Smart Citation
“…The effect of bulges in the midB_1013 is similar to that of mismatches and wobble base pairs found in the previous study [19]. Therefore, we examined the effect of bulges in Bar charts to show the unproductive/productive ratios or cleavage efficiency (i.e.…”
Section: The Midb_89 On the 3p-strand Influences The Cleavage Sites Osupporting
confidence: 57%
“…S1A). Microprocessor interacts with multiple RNA elements within pri-miRNAs in order to ensure that its double cleavage occurs both accurately and efficiently [12][13][14][15][16][17][18][19][20]. These RNA elements can be classified into two groups, primary RNA sequencing motifs and secondary RNA structures.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple RNA elements (including UG, UGU, mGHG, seedMW, midMW, CNNC, and AIL), are known to affect the cleavage state of Microprocessor via either DROSHA or DGCR8 (Auyeung et al, 2013;Fang and Bartel, 2015;Nguyen et al, 2015;Kim et al, 2018;Nguyen et al, 2018;Kwon et al, 2019;Nguyen et al, 2019;Dang et al, 2020;Li et al, 2020;Nguyen et al, 2020). We have previously demonstrated that the action of an RNA element is dependent on its position.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of DGCR8 at the loop also prevents DROSHA from interacting with the apical junction. In addition, a midMW, which is frequently present in the upper stem of human pri-miRNAs, inhibits the unproductive cleavage by DROSHA (Li et al, 2020). The inhibition of unproductive cleavage by these mechanisms increases the chance of productive cleavages by Microprocessor.…”
Section: Introductionmentioning
confidence: 99%
“…The apical loop connects to one end of the stem via the apical junction, whereas two ssRNA segments, namely the 5p-and 3p-basal segments, flank the other end, making a basal junction 2,15 . Pri-miRNAs contain several RNA elements, such as UG, UGU, mGHG, CNNC, seedMW, and midMW, which are critical for the efficiency and accuracy of pri-miRNA processing by Microprocessor 8,10,17,[22][23][24][25][26][27][28] . The recent report demonstrated that the internal loop in the lower stem of pri-miRNAs facilitates the single cleavage of pri-miRNAs on the 5p-strand and reduces the double cleavages of Microprocessor, thereby controlling miRNA biogenesis 29 .…”
mentioning
confidence: 99%